Financial Performance Analysis Reviewed from Liquidity, Solvency and Profitability Aspects - Widianingrum, Enggar; Suryani, Rani; Ilmaknun, Lulu (Institut Bisnis dan Informatika Kesatuan, 2024)
This research was conducted to analyze the financial ratios of PT Berlina Tbk during the period 2019 to 2022 see the company’s ability to use ratios. This research uses secondary data by utilizing financial reports and company reports. The analytical tool used in this research is liquidity, solvency, and profitability ratios. Based on the results of this research, it can be seen that the level of PT Berlina Tbk liquidity ratio, which is assessed by the average current ratio of 71,04%, cash ratio of 6,06%, and quick ratio of 44,16%, is considered illiquid. The solvency level of PT Berlina Tbk, which is assessed from the average debt to assets ratio of 59,57%, debt to equity ratio of 147,80%, and long-term debt to equity of 64,38%, is also considered not solvable, where the average calculation results the ratio is in poor condition and does not meet industry ratio standards. And for PT Berlina Tbk profitability level which is assessed from an average gross profit margin of 3,43%, net profit margin of 15,43%, and return on assets of 8,40%, which is considered less efficient, there needs to be a policy so that the profits obtained are more efficient.